Critical Discourse Analysis of Justice Concepts in the Holy Quran [In Arabic] - Seyedeh Saeedeh Mirhaghjoo Langroodi; Mohammad Saadi (زبان کاوی کاربردی)
Justice is one of the core and fundamental concepts in the value and cognitive structures of divine religions in general and Islam in particular. It has a central position in Quranic discourse—not as a temporary moral value, but as a universal principle permeating all levels of Islamic understanding of the world, humanity, society, and legislative as well as existential relations. This study aims to analyze the concepts related to justice in the Holy Quran using two approaches: critical discourse analysis (CDA) and cognitive linguistics. CDA examines how this abstract concept is constructed and applied in linguistic, social, and moral contexts. Norman Fairclough’s (1995) model argues that language is not only a tool for transmitting information but also plays a role in creating meaning, shaping social reality, and reinforcing values and ideologies. The study focuses on Quranic keywords such as justice (ʿadl), fairness (insaf), truth (ḥaqq), and balance (mīzān). Cognitive linguistic tools, especially conceptual metaphors, are used to reveal how justice is conceptualized in human cognition, including metaphors such as “Justice = Balance”, “Justice = Light”, and “Justice = Straight Path”. Discourse contrasts such as “justice vs. oppression” and “fairness vs. injustice” are also analyzed to demonstrate their practical functions in the Quranic context. The results indicate that justice in the Quran is not merely a legal principle or legislative framework but a comprehensive cognitive and ethical value reflecting the unity of the Quranic structure, the centrality of monotheism, and its ideological and cognitive significance. The semantic structures of these selected terms also influence Quranic consciousness, guiding audiences toward a holistic understanding of justice as a core Islamic value